Cardiac Contractility Modulation Device and Subcutaneous Implantable Cardioverter Defibrillator Combination: A New Hope for Heart Failure Patients with Low Ejection Fraction and Narrow QRS Complex - Bandar Al-Ghamdi; Azam Shafquat; Yaseen Mallawi (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2016)
Heart failure is a common cardiovascular disease with a high morbidity and mortality despite advances in medical and devicerelated management. Cardiac resynchronization therapy (CRT) which is also known as biventricular pacing has proven to be an effective treatment in heart failure [1-6]. However, CRT is  generally recommended for patients in sinus rhythm and prolonged QRS complex (≥ 120 ms) with left bundle branch block (LBBB), or a QRS complex width of ≥ 150 ms in the absence of LBBB [6]. On the other hand, only 30-40% of all heart failure patients show such a prolonged QRS complex [7,8] and therefore the 60-70% of patients who have a normal QRS complex cannot be treated with CRT. Furthermore, around 30% of the patients eligible for CRT treatment do not respond to CRT [7,8].